Are analysts recommendations associated with management's earnings forecasts? / Vahid Biglari - Biglari, Vahid (2014)

(untitled)
The opportunistic and efficiency views of the forecasts undertaken by managers are completely different. In the efficiency approach, it is believed that by providing accurate forecasts, management provides correct information to the market, thereby restricting them to do earnings management. Therefore forecasts are truthful. In contrast, the opportunistic view of forecasts is that management s forecasts consist of biased signals. Managers will use earnings and Forecasts Management (FM) as tools to create positive earnings surprises that will lead to temporary stock price appreciation or preventing stock price depreciation. This research shows that as indicated by the companies growth capabilities the Analysts Recommendations (AR) can explain the difference in behaviours of managers under these two views. This research highlights the managers decision in reporting pessimistic forecast to produce positive Forecasts Errors (FEs) when a company s shares are recommended to sell (hereafter called sell companies), and generate optimistic forecast when a company s shares are recommended to buy (hereafter called buy companies). Previous researches show that buy (growth) companies conduct income increasing earnings management in order to meet forecasts and generate positive forecast Errors (FEs). This behavior however, is not inherent in sell (non-growth) companies. By referring to the existing framework in the literature, this research hypothesizes that since sell companies are pressured to avoid income increasing earnings management, they are more capable and inclined to pursue income decreasing FM in order to produce positive FEs. IV Using a sample of 2576 firm- years of companies that are listed on the NYSE on years 2009 and 2010, the study discovers that sell companies conduct income decreasing FM to produce positive FE. However, the frequency of positive FEs of sell companies is not higher than that of buy companies. In addition, in the sell companies group, the companies that have positive forecasts errors issue higher pessimistic forecasts. Such pessimistic forecasts lead to higher positive forecasts errors. However, in the buy companies group, the companies that have positive forecasts errors do not issue higher pessimistic forecasts. Such pessimistic forecasts do not lead to higher positive forecasts errors. Consistent with the efficiency perspective, the study suggests that even though buy and sell companies are highly motivated to avoid negative FEs, they exploit different but efficient strategies in order to meet their respective forecasts. The findings of this research adds to the previous researches by proving that not only the buy companies (which are supposed to be growth companies) engage in income increasing earnings management to realize positive forecast error, but sell (non-growth) companies engage in negative forecast management to accomplish similar goals. Furthermore, the findings help us understand the complexities behind informative and opportunistic forecasts that fit under efficiency versus opportunistic theories in the literature.